Electronic Structure Study of Various Transition Metal Oxide Spinels Reveals a Possible Design Strategy for Charge Transport Pathways. Issue 4 (1st April 2022) - Elbaz, Yuval; Rosenfeld, Avia; Anati, Noam; Caspary Toroker, Maytal
Abstract : The charge transport properties in solids play an important role in the selection of materials for electrochemical devices. Spinels are a special class of solids that are very versatile and possess different properties based on changes in stoichiometry and cation distribution. In that way, their properties can be tailored to fit certain uses. Here we report a density functional theory study of the electronic structures of nine normal and inverse ternary AB2 O4 (A, B = Fe, Co, Ni, Mn) and A3 O4 spinels. We found that changing the cation distribution of CoMn2 O4 into (Mn)[CoMn]O4 lowers the bandgap by about three times. Additionally, charge transport occurs mostly through octahedral sites while in (Co)[CoNi]O4 it occurs through tetrahedral sites. Bulk-based band alignment results are also reported for the spinels in this work in order to design materials with preferred charge transport pathways.